The dramatic structure in the poetry of Maitham Radhi: A study of a collection of bad words (Journal of Imam Al-Kadhim College, 2025)
"Bad Words" is a collection of poetry by the Iraqi poet Maitham Radhi. The book was published in three editions, in 72 medium-sized pages, as part of the "Innocence" series published by Mediterranean Publications in Italy. Iraqi poet Maitham Radhi opens his collection "Bad Words" with the poem "Stuttering," as if it were an apology, a preliminary justification, like someone embarking on a dangerous adventure and fearing failure. This is not because he doubts his talent, but because the subject he chose for all his poems—"war"—touches him personally. He lives it, clings to it, and feels it to the point that he becomes morally confused when his self approaches the subject, to the point of separating them.
Keywords: Dramatic structure; Bad words; War; Free verse; Dramatic structure, Bad words, War, Free verse, Stuttering; Stuttering